(untitled) (Journal of Cancer Research Updates, 2019)
Background: Liver abscesses are uncommon, but they are associated with a hospital mortality rate of 10% in patients without cancer. However, its relevance in cancer patients in terms of survival and length of hospitalization is unknown. Patients and Methods: We conducted an observational study in order to analyze the impact of liver abscesses in hospitalized cancer patients. Eligible patients were adults with a solid tumor, received antineoplastic treatment and were hospitalized in our department with a diagnosis of liver abscesses. Primary end-points of the study were overall survival (OS) and mean hospital stay (MHS). Secondary end-points were the description of risk factors of liver abscesses, isolated microorganisms and the specific treatment. Results: In our study the incidence of liver abscesses in cancer patients was 1.18%. Median age was 63 years, 60% were men, and the vast majority of patients had an advanced bilio-pancreatic tumor (85%). With a median follow-up of 18 months, median OS was 6 months (95% CI: 1-11); and OS probability at 18-month was 19%. MHS was 27.2 days (95% CI: 20.3-40.7). Risk factors for developing liver abscesses were: a) bilio-pancreatic cancers; b) chemotherapy administration; c) severe malnutrition; and d) biliary drainage/prosthesis. Ten patients (50%) had bacteremia, and the most common isolated microorganism was E.coli (30%). Percutaneous drainage of abscesses was performed in 40% of the patients, and all patients were treated with broad-spectrum antibiotics. Conclusions: Although liver abscesses were uncommon, they were associated with a prolonged hospitalization and poor outcome in cancer patients.